Initial presentation of acute myelogenous leukemia in the infiltrate underlying an actinic keratosis - Collin Blattner; Andrea DeDonato; Elen Blochin; Viktoryia Kazlouskaya; Dirk M Elston (Wolters Kluwer Medknow Publications, 2014)
We report an 85-year-old female patient who presented with an erythematous keratotic lesion on her temple suspicious of squamous cell carcinoma. Histological evaluation revealed actinic keratosis, but the underlying atypical infiltrate contained atypical myeloid forms consistent with acute myelogenous leukemia (AML). Upon further questioning, it was determined that the patient had a history of myelodysplastic syndrome. Her skin biopsy provided the first evidence of progression to AML. This case serves as an important reminder of the role the dermatopathologist plays in identifying serious systemic disease.